A STANDARD STUDY TO DETERMINE THE NATURE OF THE RELATIONSHIP BETWEEN THE INFLATION RATE AND THE UNEMPLOYMENT RATE -IN ALGERIA DURING THE PERIOD (1970-2021) USING THE ERROR CORRECTION MODEL (ECM)- - Messaoud, Lecheheb; Ali, Bellarou (The journal of contemporary issues in business and government, 2024)
This study aims to analyze and measure the relationship between the inflation rate and the unemployment rate in Algeria during the period (1970-2021), using the error correction model (ECM), data obtained from specialized bodies, such as the National Bureau of Statistics, the International Monetary Fund, and the World Bank.The study found that the relationship between the inflation rate and unemployment in Algeria during the period (1970-2021) is a one-way direct relationship, starting from the inflation rate to the unemployment rate, as An increase in the inflation rate by 1% leads to an increase in the unemployment rate by 1.98%, a result that negates the application of the Phillips curve to the Algerian economy during the study period.